What can we learn from consumer reports on psychiatric adverse drug reactions with antidepressant medication? Experiences from reports to a consumer association - Vilhelmsson, Andreas (BioMed Central, 2011)
BACKGROUND: According to the World Health Organization (WHO) the cost of adverse drug reactions (ADRs) in the general population is high and under-reporting by health professionals is a well-recognized problem. Another way to increase ADR reporting is to let the consumers themselves report directly to the authorities. In Sweden it is mandatory for prescribers to report serious ADRs to the Medical Products Agency (MPA), but there are no such regulations for consumers. The non-profit and independent organization Consumer Association for Medicines and Health, KILEN has launched the possibility for consumers to report their perceptions and experiences from their use of medicines in order to strengthen consumer rights within the health care sector. This study aimed to analyze these consumer reports. METHODS: All reports submitted from January 2002 to April 2009 to an open web site in Sweden where anyone could report their experience with the use of pharmaceuticals were analyzed with focus on common psychiatric side effects related to antidepressant usage. More than one ADR for a specific drug could be reported. RESULTS: In total 665 reports were made during the period. 442 reports concerned antidepressant medications and the individual antidepressant reports represented 2392 ADRs and 878 (37%) of these were psychiatric ADRs. 75% of the individual reports concerned serotonin-reuptake inhibitor (SSRI) and the rest serotonin-norepinephrine reuptake inhibitor (SNRI). Women reported more antidepressant psychiatric ADRs (71%) compared to men (24%). More potentially serious psychiatric ADRs were frequently reported to KILEN and withdrawal symptoms during discontinuation were also reported as a common issue. CONCLUSIONS: The present study indicates that consumer reports may contribute with important information regarding more serious psychiatric ADRs following antidepressant treatment. Consumer reporting may be considered a complement to traditional ADR reporting.